Peran Public Relation Pada Lembaga Non-Profit Ruang Belajar Aqil - Choirul Miftakhul Anam; Yanda Bara Kusuma (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
Young people have an active role in moving a society. So create a social environment that aims at one. In society or organization, communication becomes important. In any institution the role of public relations is important as a liaison and image-building on the outside. In a non-profit institution, the Aqil Study Area has public relations organized as a social division. It's interesting to study his role as a public relations in a non-profit organization. This research uses the qualitative type of work done during the internship for about a semester. Research results show that the public role of relations to image on the outside is shaped through the development and collaboration of partnerships. Its activities focused on establishing sustainable cooperation with the government and colleges.